PENGARUH PENGGUNAAN TEPUNG CACING TANAH (Lumbricus rubellus) TERHADAP KECERNAAN BAHAN KERING DAN BAHAN ORGANIK RANSUM DOMBA LOKAL JANTAN - Ginda Sihombing; Wara Pratitis; Ginanjar Arya Dewangga (Caraka Tani: Journal of Sustainable Agriculture, 2010)
The development of sheep livestock is done as a comodity producer to meet the need of the meat. To increase the productivity of the sheep, the feed have a certain quality with the mix of worm flour. This research aims to determine the influence of the use of worm flour (Lumbricus rubellus) concerning to dry and organic matter digestibility lokal male sheeps feed. This research was conducted in the enclosure of research at the Faculty of Agriculture, Animal Husbandry Department of the Universitas Sebelas Maret Surakarta which is located in the Village Jatikuwung, Gondangrejo District, District Karanganyar. Research was conducted from December 28th, 2008 to February 22nd, 2009 using the 12 local male tail sheep with body weight on average 13.82 ± 0.73 kg / head. Feed given at 6% of body weight consist of a concentrate forage and comparison with 70:30 per cent (basic dry matter). Utilized of the concentrate made of a mixture that consist of bekatul, oilcake soybean, corn flour, worm flour, and premix while forage given a field grass. Feed treatment used field grass 70%, concentrate 30% (P0); field grass 70%, 28% concentrate, worm flour 2% (P1); field grass 70%, 26% concentrate, worm flour 4% (P2) and 70% field grass, 24% concentrate, worms flour 6% (P3). Experimental design used was the Complete Random Design (CRD) pattern, the direction of the 4-level treatment (P0, P1, P2, and P3). Each treatment consist of 3 test replications and the replications each of one local male sheep. Parameter observed: dry matter consumption (DMC), organic matter consumption (OMC), dry matter digestibility (DMD), and organic matter digestibility (OMD). Results of research indicate that the average of the four treatment (P0, P1, P2 and P3) respectively for the dry matter consumption 858.35, 876.57, 881.55 and 887.58 (grams/ head/ day), organic matter consumption 670.32, 682.04, 686.16 and 689.03 (grams/ head/ day), dry matter digestibility 55.17, 59.51, 57.19 and 58.84 percent and organic matter digestibility 66.28, 69.09, 67.21 and 68.12 percent. Variansi analysis results show that the dry matter consumption, organic matter consumption, dry matter digestibility, and organic matter digestibility is not significantly different (P ≥ 0.05). Conclusion of this research is the use of worm flour (Lumbricus rubellus) in feed up to 6% of the total concentration does not affect consumption and digestibility of dry and organic matter, but able to maintain the quality oflocal male sheep feed.